2004
DOI: 10.1023/b:biom.0000027700.90780.45
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic activity of bovine lactoferrin

Abstract: Bovine lactoferrin catalyzes the hydrolysis of synthetic substrates (i.e., Z-aminoacyl-7-amido-4-methylcoumarin). Values of Km and kcat for the bovine lactoferrin catalyzed hydrolysis of Z-Phe-Arg-7-amido-4-methylcoumarin are 50 microM and 0.03 s(-1), respectively, the optimum pH value is 7.5 at 25 degrees C. The bovine lactoferrin substrate specificity is similar to that of trypsin, while the hydrolysis rate is several orders of magnitude lower than that of trypsin. The bovine lactoferrin catalytic activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…1c) was reported for mast cells alpha-chymase in conjunction with the attenuation of allergic response [55]. Two cleavage sites at the edges of the β-strands were reported for lactoferrin (Fig.5a) as a result of autoproteolytic activity of this iron binding protein associated with mammalian non-immune defense against pathogens [56]. Cleavage of an internal strand of a β-sheet, which, at the same time, is the N-terminus of the protein, was registered for actin and two different types of proteases (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…1c) was reported for mast cells alpha-chymase in conjunction with the attenuation of allergic response [55]. Two cleavage sites at the edges of the β-strands were reported for lactoferrin (Fig.5a) as a result of autoproteolytic activity of this iron binding protein associated with mammalian non-immune defense against pathogens [56]. Cleavage of an internal strand of a β-sheet, which, at the same time, is the N-terminus of the protein, was registered for actin and two different types of proteases (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…N-␣-Benzyloxycarbonyl-Phe-Arg-7-amido-4-methylcoumarin (Z-Phe-Arg-AMC) (Sigma) was used as a substrate, as described previously (42), and Lf-catalyzed hydrolysis was determined in PBS at room temperature (21°C). Lf was used at a concentration of 10 M, and the substrate concentration ranged from 1 to 200 M. The cleavage of the substrate was followed fluorometrically at 460 nm with an excitation wavelength of 355 nm by monitoring the increase with a Victor microtiter plate reader (Wallac).…”
Section: Methodsmentioning
confidence: 99%
“…The serine protease activity of aLf has been described extensively previously (33,42,52,57,68). To test whether this activity was responsible for S. aureus killing, aliquots of bovine aLf and human aLf were treated with PMSF, a potent inhibitor of serine proteases, and used in killing assays.…”
Section: Isda Is An Lf Binding Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that Lf blocks Enteropathogenic E. coli adherence, hemolysis and induction of actin polymerisation in HEp2 cells as a result of the Lf-mediated degradation of E. coli secreted proteins A, B and D (EspABD) [63,64]. Massucci et al [65] characterised in vitro the proteolytic activity of bovine Lf towards synthetic substrates. The substrate specifi city is similar to that of trypsin, and serine protease inhibitors inhibit this catalytic activity, although the values of the catalytic parameters (k cat , K m ) are several orders of magnitude lower than those of trypsin.…”
Section: Antibacterial Activity Related To Proteolysismentioning
confidence: 99%